2022
DOI: 10.3390/cells11233785
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2-Associated ssRNAs Activate Human Neutrophils in a TLR8-Dependent Fashion

Abstract: COVID-19 disease is characterized by a dysregulation of the innate arm of the immune system. However, the mechanisms whereby innate immune cells, including neutrophils, become activated in patients are not completely understood. Recently, we showed that GU-rich RNA sequences from the SARS-CoV-2 genome (i.e., SCV2-RNA1 and SCV2-RNA2) activate dendritic cells. To clarify whether human neutrophils may also represent targets of SCV2-RNAs, neutrophils were treated with either SCV2-RNAs or, as a control, R848 (a TLR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…However, in the HEK293 NF-κB luciferase reporter assays, the activation of hTLR7 by SAMPs is far less significant than that of hTLR8. In neutrophiles, the activation of hTLR8 but not hTLR7 is observed 52 . Further, in an acute graft-versus-host disease study, serum miR-29a has been shown to be able to activate mTlr7 in mouse DCs and hTLR8 in human DCs 44 .…”
Section: Discussionmentioning
confidence: 98%
“…However, in the HEK293 NF-κB luciferase reporter assays, the activation of hTLR7 by SAMPs is far less significant than that of hTLR8. In neutrophiles, the activation of hTLR8 but not hTLR7 is observed 52 . Further, in an acute graft-versus-host disease study, serum miR-29a has been shown to be able to activate mTlr7 in mouse DCs and hTLR8 in human DCs 44 .…”
Section: Discussionmentioning
confidence: 98%
“…At least partially, this activation of PMNs could be directly determined by the virus. It was recently described by [45], that single-strand RNAs from the SARS-CoV-2 genome is able to activate human neutrophils via TLR8, triggering a remarkable production of TNFα, IL-1ra, and CXCL8, apoptosis delay, modulation of CD11b and CD62L expression, and release of neutrophil extracellular traps. This exuberant contribution of PMNs to the interstitial pneumonia that occurs in COVID-19 was, in many aspects, reproduced in hACE2 mouse model infected with SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…This activation of PMNs could be directly determined by the virus. It was recently described [ 53 ] that single-strand RNAs from the SARS-CoV-2 genome are able to activate human neutrophils via TLR8, triggering a remarkable production of TNF-α, IL-1ra, and CXCL8, apoptosis delay, the modulation of CD11b and CD62L expression, and the release of NETs. Additionally, the tissue damage induced by the neutrophilic infiltration can activate the inflammasome, as described above, resulting in more inflammation and neutrophil recruitment, perpetuating, therefore, the inflammatory process.…”
Section: Discussionmentioning
confidence: 99%